1998
DOI: 10.30541/v37i4iipp.705-725
|View full text |Cite
|
Sign up to set email alerts
|

Gender Dimensions of Demographic Change in Pakistan

Abstract: The achieving of equality and equity between men and women in different spheres of life is essential for the attainment of sustainable development goals. In this context, the need for enhancement of women’s participation in national development programmes and their full integration into the development process has been widely recognised in various global and regional forums. More recently, the Programme of Action adopted by the International Conference on Population and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
1
Order By: Relevance
“…Contrary to the general observations and expectations, the results of this study, as mentioned earlier, suggest that on the whole there do not appear to be any gender differentials in the provision of health care. This is so in spite of the fact that many studies in Pakistan on various gender-related issues have shown significant gender bias in favour of male children [Mahmood and Nayab (1998); Sathar and Kazi (1997); Ali (1989)]. Thus, one may conclude that parental altruism prevails at least in the provision of health care to sick children.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the general observations and expectations, the results of this study, as mentioned earlier, suggest that on the whole there do not appear to be any gender differentials in the provision of health care. This is so in spite of the fact that many studies in Pakistan on various gender-related issues have shown significant gender bias in favour of male children [Mahmood and Nayab (1998); Sathar and Kazi (1997); Ali (1989)]. Thus, one may conclude that parental altruism prevails at least in the provision of health care to sick children.…”
Section: Discussionmentioning
confidence: 99%
“…Men participate more in the formal outside-home affairs and decision-making in the community, while women tend to play a major role within home in terms of nurturing of children and maintenance of household. Overall, gender inequality in social and economic spheres is evident from the wide gap between male and female literacy and educational attainment (especially in rural areas), low female work participation in the formal sector, and high mortality among girl children (1-4 years) and mothers [Mahmood and Nayab (1998)]. People living in different regions/provinces speak their own local languages, especially in rural areas, and can be distinguished by their distinct ethno-linguistic groups and social customs.…”
Section: Socio-cultural Backgroundmentioning
confidence: 99%
“…They have gained disproportionately from the development process. Pakistan needs to go a long way to achieve a balanced and sustainable development scenario (Mahmood and Durr-e-Nayab, 1998). For women, the access to money-earning activities, amongst others is one of the important means to improve their position (Polachek and Robst, 1997).…”
Section: Introductionmentioning
confidence: 99%